Quantifying the Stress in Stress Radiographs to Determine Sufficient Laxity of the Coxofemoral Joint: A Canine Hip Dysplasia Cadaveric Study - Vandekerckhove, Louis M.J.; Herregodts, Stijn; Saunders, Jimmy H.; Broeckx, Bart J. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective While it has been known for a long time that laxity in the hip joint is the primary cause of degenerative changes later on in canine hip dysplasia, limited data are available on the fundamental characteristics that define the procedure used to quantify this. The aim of this study was to evaluate the force–laxity relation to assess the repeatability of repeated cycles of stress on the hip joint and determine the force necessary tomeasure a sufficient proportion of laxity present in hip joints.Materials and Methods Thirty-four canine cadavers underwent a radiographic protocol including stress radiographs with increasing force using the Vezzoni modified Badertscher distension measuring device (VMBDmD). Three dogs underwent five repeat examinations. The laxity index (LI) and osteoarthritis were scored.Results and Conclusion The curves and the maximal LI (LImax) were not significantly influenced by osteoarthritis, weight, gender, and side. The position of the VMBDmD influenced the curve but not the LImax. The force–laxity curve itself and the LImax were repeatable, which indicated that it did not cause permanent damage to the joint and also confirmed the practicability of the procedure. Ninety percent of hip joints reached sufficient laxity at a force of 95.32 N, which is realistically achievable. Further studies are necessary before extrapolating these results to patients and to further enlighten the biomechanics of stress radiographs.
Keywords: canine hip dysplasia; VMBDD; laxity; force; fulcrum